Área de vida e biologia reprodutiva da maria-da-restinga (Phylloscartes kronei) (Aves, Tyrannidae) - Gussoni, Carlos Otávio Araújo [UNESP] (2014)
Little is known about natural history of the globally threatened Restinga Tyrannulet (Phylloscartes kronei). This work aimed to describe its home range and territory, and collect new information about its breeding biology. We captured and banded with coloured bands 28 individuals at Reserva Bicudinho-do-brejo (Guaratuba, PR) and four at Parque Natural Municipal da Lagoa do Parado. Field work was conducted monthly from January 2012 to December 2013, comprising 211 days of field observations. The individuals home range size was 1.76 ± 0.93 ha and the home range size of pairs was 2.52 ± 1.91 ha. There weren´t differences between the home range size of males and females and the home range size of individuals and pairs throughout the study. In 2012 we found different home range size of the individuals inside and outside the breeding season, whereas this was not observed in 2013. The home range size of pairs did not vary inside and outside the breeding season. We found extensive overlapping on home range. The territory size was recorded for two adjacent pairs: 0.68 and 0.46 ha. We surveyed individuals in a 21 ha area and obtained a density of 1.04 pairs/ha. The breeding season started in September and the last signs of reproduction were recorded in January. Nests were built between 0.72 and 3 m above the ground. All nests were closed ovoids internally built with dry leaves and externally lined with green mosses. The materials were glued with spider web and the oological chamber lined with soft seeds. The predation rate was 60% and the Mayfield success for the incubation period was 42.42%. One pair whose nest was predated built another nest 52 meters away. The second nest was predated and the pair built another one 93 meters away. Other pair whose nest was predated built a new nest 51 meters away. It took about 19 days to build the nests and they were all made by females. The clutch size varies from 2 to 3 white eggs (15.9 – 16.8 mm x...